Efektivitas Penggunaan Platform Portofolio Behance Untuk Evaluasi Pembelajaran di SMK Sebagai Implementasi Merdeka Belajar - Nadana, Nafisah Hasya; Maya Purnama Sari (Center of Language and Cultural Studies, 2023)
Evaluation of learning is a factor of student learning success in order to be able to compete in the modern era. In line with technological developments, portfolio-based learning evaluation using the Behance portfolio platform fits with the Merdeka Learning curriculum concept for vocational high school students (SMK). For this reason, this study aims to determine the effectiveness of using the behance portfolio platform for evaluating learning in SMK as the implementation of Merdeka Learning using a quantitative approach with data to be taken from teachers and students at SMK Negeri 3 Bandung.